Principles of leadership - DuBrin, Andrew J. (South-Western Cengage Learning, 2013)
1. The Nature and Importance of Leadership. 2. Traits, Motives, and Characteristics of Leaders. 3. Charismatic and Transformational Leadership. 4. Leadership Behaviors, Attitudes, and Styles. 5. Contingency and Situational Leadership. 6. Leadership Ethics and Social Responsibility. 7. Power, Politics, and Leadership. 8. Influence Tactics of Leaders. 9. Developing Teamwork. 10. Motivation and Coaching Skills. 11. Creativity, Innovation, and Leadership. 12. Communication and Conflict Resolution Skills. 13. Strategic Leadership and Knowledge Management. 14. International and Culturally Diverse Aspects of Leadership. 15. Leadership Development and Succession.